2017
DOI: 10.1038/ncomms14916
|View full text |Cite
|
Sign up to set email alerts
|

Energy efficiency to reduce residential electricity and natural gas use under climate change

Abstract: Climate change could significantly affect consumer demand for energy in buildings, as changing temperatures may alter heating and cooling loads. Warming climates could also lead to the increased adoption and use of cooling technologies in buildings. We assess residential electricity and natural gas demand in Los Angeles, California under multiple climate change projections and investigate the potential for energy efficiency to offset increased demand. We calibrate residential energy use against metered data, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
90
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 143 publications
(93 citation statements)
references
References 45 publications
(55 reference statements)
2
90
0
1
Order By: Relevance
“…Primarily, none of the models identified are developed to support continuous updating, with the majority of studies being a single-time snapshot of scenarios. [24][25][26][27][28][29][30] Climate change mitigation will be a decades-long effort, and developing effective mitigation strategies will require models that are regularly updated with the best available data on a range of exogenous factors-technology R&D investment and technology commercialization, changes in the electricity generation mix, and evolving consumer behavior and preferences. Secondly, many of the studies identified use a top-down approach, which aggregates the total savings available from the buildings sector and focuses on macroeconomic trends rather than specific policy-or technology-driven savings.…”
Section: Context and Scalementioning
confidence: 99%
“…Primarily, none of the models identified are developed to support continuous updating, with the majority of studies being a single-time snapshot of scenarios. [24][25][26][27][28][29][30] Climate change mitigation will be a decades-long effort, and developing effective mitigation strategies will require models that are regularly updated with the best available data on a range of exogenous factors-technology R&D investment and technology commercialization, changes in the electricity generation mix, and evolving consumer behavior and preferences. Secondly, many of the studies identified use a top-down approach, which aggregates the total savings available from the buildings sector and focuses on macroeconomic trends rather than specific policy-or technology-driven savings.…”
Section: Context and Scalementioning
confidence: 99%
“…Reduction in energy cost for households leading to improved savings for other things. This would create job opportunities for the local people (Reyna and Chester, 2017).…”
Section: List Of Figuresmentioning
confidence: 99%
“…Despite the rich literature in electricity demand prediction 2,[20][21][22][23] , little prior work has focused on exploring the climate sensitivity of demand with respect to different measures of heat beyond air temperature. While climate science research establishes air temperature as an incomplete measure of the surface heat content 9,10,18,24,25 , the majority of the existing research on climate-demand nexus use air temperature -or features derived from air temperature, such as cooling and heating degree days-as key predictors 2,[26][27][28] .…”
mentioning
confidence: 99%